Mám Éan, Co. Galway, Ireland: a record of Holocene vegetation and landscape change from upland Connemara - Michael O extquotesingleConnell; Chun Chang Huang (PANGAEA, 2020)
A small corrie lake, at Mám Éan, i.e. Maumeen (anglicised version of name; at 245 m asl), in the Maumturk Mountains, Connemara, provides a record of woodland dynamics and human impact that spans the Holocene. The record includes pollen, macrofossil and charcoal data, results of whole core and single-sample magnetic measurements, and loss-on-ignition data. The chronology relies mainly of 14C dates (conventional and AMS) for the 4.3 m long lake core. Two conventional 14C dates for bog-pine timbers collected near the lake are also provided. Main findings The course of vegetation development at Mám Éan follows the broad outline of that recorded from lowland Connemara and other sites in western Ireland. The importance of pine (Pinus sylvestris) during the early and mid-Holocene (ca. 10.2-4.8 ka) is demonstrated. The first substantial opening-up of the landscape occurred as a result of human activity in the early Neolithic (ca. 5.6 ka). This is envisaged as occurring mainly in the lowlands. After a farming phase (mainly pastoral) that lasted over 200 years, woodland regeneration followed that involved most trees but especially pine. Later yew (Taxus) spread and expanded largely at the expense of pine which by 4.7 ka had ceased to be the local dominant, never regained its importance and probably became regionally extinct before 2 ka. A major reduction in woodland began at ca. 4.5 ka, i.e. towards the end of the Neolithic, in the context of increased farming. Further substantial reductions took place at ca. 3.5 ka and 2.3 ka, again in the context of increased human activity in the mid-Bronze Age and Iron Age (La Tène period), respectively. It was not, however, until the late Medieval period (ca. AD 1200) that the present treeless aspect came about, again in the context of substantial farming. Three soil erosional phases were detected. In the early Holocene, soils had stabilised by ca. 10 ka with the development of more or less full woodland cover. The first erosion phase occurred at 9.2 ka and was accompanied by fluctuations in Pinus and Corylus that may indicate a climate oscillation of regional significance. A second erosion event is recorded at 6.4 ka which is not distinctly reflected in the pollen data. It may be the result of a weather event rather than a sustained shift in climate. In the upper part of the profile, i.e. starting at ca. AD 800, strong erosion is recorded. This is connected with the final stages of deforestation and increasing use of the uplands for pastoral farming. The uppermost sediments are highly organic which presumably reflects increased peat erosion, the result of a sharp increase in sheep numbers that began in the mid-1970s. There are records (pollen / spore) for local presence of biogeographically interesting species including Osmunda regalis, Hymenophyllum (probably exclusively H. wilsonii), Diphasiastrum alpinum and Eriocaulon aquaticum. There are also frequent but mainly single-pollen records for trees such as Tilia, Fagus and Tsuga that are ascribed to long-distance pollen transport. Photographs, including scans of photographs taken on site on coring day, are provided in a pdf file.